Antidepressants with a high serotonin reuptake transporter affinity and serum lipid levels in a population-based study in older adults. (October 2015) - Noordam, Raymond; Aarts, Nikkie; de Keyser, Catherine E; Hofman, Albert; Stricker, Bruno H; Visser, Loes E
Objective: We aimed to investigate the association between antidepressants and serum lipid levels in a population-based study in older adults. Methods: We included participants from the prospective Rotterdam Study with data on lipid levels (total, low-density lipoprotein (LDL) and high-density lipoprotein cholesterol, and triglycerides). We classified antidepressants based on binding affinity to the serotonin transporter (low/intermediate- and high-affinity antidepressants). We compared lipid levels in users of these groups of antidepressants with lipid levels in non-users. Furthermore, we studied effect modification by the 102C>T polymorphism ( HTR2A gene), which is associated with antidepressant drug response and metabolic outcomes. Results: Compared with non-users ( N = 6438), LDL cholesterol level was higher (2.9 versus 3.1 mmol/L, respectively; p = 0.05) in users of high-affinity antidepressants ( N = 89). Similar levels of the other lipids were observed between the groups for the other lipids. The mean difference in serum LDL cholesterol level between non-users and users of high-affinity antidepressants was largest in participants with the CC genotype compared with the other genotypes (notably 0.47 mmol/L), indicative of effect modification ( p -value for interaction = 0.03). Conclusion: Antidepressants with a high serotonin reuptake transporter affinity were associated with higher LDL cholesterol levels, which were modified by a common genetic variation in the HTR2A gene.